2022
DOI: 10.1096/fj.202200111r
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with isoleucine or valine corrects hyperinsulinemia and reduces intrahepatic diacylglycerols, liver steatosis, and inflammation in Ldlr−/−.Leiden mice with manifest obesity‐associated NASH

Abstract: Non‐alcoholic steatohepatitis (NASH) is associated with a disturbed metabolism in liver, insulin resistance, and excessive accumulation of ectopic fat. Branched‐chain amino acids (BCAAs) may beneficially modulate hepatic lipids, however, it remains unclear whether individual BCAAs can attenuate already established NASH and associated oxidative‐inflammatory stress. After a 26 weeks run‐in on fast food diet (FFD), obese Ldlr−/−.Leiden mice were treated for another 12 weeks with either valine or isoleucine (3% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
(175 reference statements)
1
13
0
Order By: Relevance
“…Previous studies from our laboratory indicated that optimal valine supplementation in the diet of sows could improve the weaning weight of piglets by increasing the milk fat synthesis in sows 24 , indicating that valine is closely related to fat metabolism in sow mammary glands. Recent studies in humans and rats have highlighted that the blood valine level may indicate whether lipid metabolism is balanced 25 , 26 . Although valine has been extensively studied considering the intestinal health of piglets 27 , the mechanism by which valine regulates the intestinal health of piglets is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory indicated that optimal valine supplementation in the diet of sows could improve the weaning weight of piglets by increasing the milk fat synthesis in sows 24 , indicating that valine is closely related to fat metabolism in sow mammary glands. Recent studies in humans and rats have highlighted that the blood valine level may indicate whether lipid metabolism is balanced 25 , 26 . Although valine has been extensively studied considering the intestinal health of piglets 27 , the mechanism by which valine regulates the intestinal health of piglets is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to exercising mice that did not receive BCAA supplementation, mice that both exercised and received BCAA supplementation exhibited a higher eWAT mass as a proportion of their total body weight. This result differs from the effects of isoleucine or valine monotreatment in Ldlr−/−.Leiden mice on a fructose-containing HFD [ 80 ]. In contrast, Zhang et al demonstrated that BCAA supplementation attenuated HFD-induced weight gain and decreased adipose tissue accumulation at the expense of abnormal lipolysis [ 81 ].…”
Section: Discussionmentioning
confidence: 73%
“…Besides, valine was reported to improve liver diacylglycerols, and reduce NASH histology with profound hepatoprotective effects on oxidative stress and inflammatory proteins (Gart et al, 2022). However, another study reported that high levels of valine could decrease gut microbiota (such as Fusobacteriota and Deferribacterota) LGZG reversed metabolites and gut microbiota, the X-axis represented metabolites, and the Y-axis represented gut microbiota, the red color showed the positive correlation, and the green color showed the negative correlation, *p < 0.05, **p < 0.01, ***p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we observed that glutamic acid was lowered in NASH and restored by LGZG decoction, and its negatively correlated gut microbiota (such as Butyricimonas and Odoribacter ) was increased in NASH and decreased by LGZG. Besides, valine was reported to improve liver diacylglycerols, and reduce NASH histology with profound hepatoprotective effects on oxidative stress and inflammatory proteins ( Gart et al., 2022 ). However, another study reported that high levels of valine could decrease gut microbiota (such as Fusobacteriota and Deferribacterota) abundances and revealed the adverse metabolic response to NAFLD, which suggested reducing dietary valine as a new approach to preventing NAFLD of laying hens ( Jian et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%